Flexor Tendon Injuries and Evaluation of Treatment Results, - Kılıç, B., Zekioğlu, A., Yücel, A. S., (My University, 2015)
Flexor tendon injury is the most commonly seen hand injury. Tendons are the structures which enable the muscles to adhere to the bones and transmit the movement starting from the muscle to the bones. They have significant role in hand movement. As treatment method, surgical repair: 1. Primary repair; 2. Secondary Repair techniques are used. With the scientific studies conducted, flexor tendon morphology, kinematics, biomechanics, biological properties and tendon improvement became quite understandable, good suturing materials were developed, and consequently successful studies regarding primary repair results were published. Flexor tendon surgery has reached its current level with the accumulation of knowledge obtained from the increased clinical and experimental studies. This study addresses flexor tendon injuries and surgical treatment methods. We achieved 76,12 % full functioning fingers in the results we obtained following the physical treatment application that started on the 10th day after primary repair that we performed in 67 patients who applied with acute flexor tendon Zone 1-2 and 3 incision. Flexion restriction and contracture developed in 16 patients (23,88 %) at various levels. Scar softening and revision surgery for contracture excision was performed in 8 patients (11,94%) with Zone 2 injury due to contracture. Superficial skin infection developed in 21 patients (31,34%) and was treated. Revision surgery was performed in 6 patients with Zone 1 injury due to rupture occurred during rehabilitation.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Flexor tendon; surgery; zone.